O Osobliwości Pewnych Niegładkich Konstrukcji Powierzchniowych (I) - Frackiewicz, H.; Legat, A. (Engineering Transactions, 1967)
The object of the considerations are non-smooth closed surfaces of certain classes. To enable the of their geometrical variability some criteria are formulated and used to determine the geometric parameters and certain relations between them, the satisfaction of which makes a surface geometrically variable. For irregular surfaces of a certain type equations are obtained describing their geometrical variability. By passing to smooth surfaces these equations become identical with those derived by V.Z. Vlasov for conical surfaces. The paper is illustrated by detailed diagrams enabling us to design correct (that is geometrically invariable) spatial surface structures.